Ways of 'Being With': Caring for Dying Patients at the Height of the COVID-19 Pandemic. Issue 1 (1st March 2021) - Driessen, Annelieke; Borgstrom, Erica; Cohn, Simon
Abstract: Palliative care professionals often speak of the importance of forming meaningful relationships with patients and their families. Trust and rapport, usually established over extended periods of time through face-to-face interactions, and a 'gentle honesty' regarding end-of-life and death are key aspects of developing a sense of intimacy with people who are approaching the end of their lives. A fundamental feature of this intimacy is conveying a sense of 'being with' a patient. However, these ways of working were greatly challenged by the impact of COVID-19. This article explores how intimacy both was and was not established at the height of the pandemic, and it describes the extent to which shared concerns functioned as a new means to create a sense of a common experience.